Good governance and ownership: A mismatch in the new EU development policy agenda - Simon Hartmann (Austrian Foundation for Development Research (ÖFSE), 2012)
The new EU development agenda is an adaptation of an old mismatch in development policy, which is the effort to join, on the one hand, donor-driven demand for good governance and democracy, and on the other hand, a commitment to the ownership of development strategies by the recipient countries. This is an ambiguity because the two approaches oppose each other. We recommend to dissolve this mismatch by promoting a new global partnership with a specific emphasis on ownership. This entails context-sensitive analyses of the political and economic environment of the transition process in partner countries.
Keywords: 330; Entwicklungshilfe; Good Governance; Entwicklungspolitik; Entwicklung; EU-Staaten